INTEGRATION OF AUGMENTED REALITY TECHNOLOGY FOR LEARNING: AN QUALITATIVE META-ANALYSIS STUDY - Maulyda, Mohammad Archi; Sugiman, Sugiman; Wuryandani, Wuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
Augmented Reality (AR) is one of the most popular technologies used in the field of education. AR technology is widely used as a learning medium or to develop engaging, innovative textbooks for students. However, there is still much debate regarding the use of AR at various levels of education, starting from elementary school to the higher education level. This qualitative meta-analysis research explores the urgency of implementing AR technology in schools and the readiness of the main subjects of learning (teachers and students) to use AR in the classroom. The synthesis method used is the narrative review model. This synthesis model is used to analyze 100 research results in non-numeric data by identifying the research results documents found. The study results show that teachers at the elementary to high school level and lecturers at the higher education level feel that AR technology is crucial to implement in the learning process. However, from all levels, teachers' and lecturers' readiness to make AR-based learning tools still needs to be improved. In addition, another finding in this study is that the percentage of teachers in elementary school (52%) readiness to use AR technology is higher than that of lecturers in higher education (21%).